Concentration of lemon pectin extract by ultrafiltration - Stechina, Damián (2012)
Current annual lemon production in Argentina is about 900 thousand t. 75% is used industrially to obtain pasteurized juice concentrate. Since 40 - 45 % of citrus fruit content is peel and seeds, the annual lemon residue yield is 360 thousand t. Lemon peel contains about 30% (B.S.) of peptic substances with an important commercial value due to its gelling and thickening properties for food, chemical, pharmacological and cosmetic products. Membrane processes have many applications in food manufacture. The objective of this study is to analyze the influence of ultrafiltration operating variables on instant permeate flow (Fp) and on the energy requirement for pectin extract concentration from lemon peel. A DDS lab module was used, lab 20-772 model with synthetic material membranes, 9 kDa, shear force, the intrinsic membrane resistance (Rm) being 3*1013 m-1. Results show that Fp decrease caused by polarization induced resistance occurrence and the influence of operating variables on Fp offer relevant data to estimate the energy requirement in relation to feeding flow at constant temperature, which may be compared to pectin concentration increase in the retained flow in relation to initial extract concentration.